Features of the Relationship between Bank Lending to Industry and Financial Sustainability of Banks - Herasymenko Alina V. (Bìznes Inform, 2022)
The article is aimed at highlighting the peculiarities concerning the impact of bank lending to industry on the financial sustainability of banks in accordance with the current tendencies in the development of the national banking sector. The article considers the current situation in the banking sector, analyzes the dynamics of the main indicators of financial sustainability of banks. It is found out, which indicators of financial sustainability of banks constituted, amongst others, the basis of the indicators of lending to industry. It is analyzed how the state of lending to industry was reflected in certain indicators of financial sustainability of banks. In particular, the dynamics of industrial shares was compared and analyzed by sectors, in terms of the gross value added of gross domestic product and in terms of the bank loan portfolio of non-financial corporations, allowing to formulate conclusions on the efficiency of the use of bank credit resources by industry and the investment return on financial resources. The analysis on the equilibrium of financial flows of banks, as well as their ability to maintain their liquidity, being important indicators of financial sustainability of banks, was carried out using the indicator of the ratio of credit and deposit funds separately for industrial enterprises, non-financial corporations, and for the system in general. The nature of the impact of inoperable credit debt of industrial enterprises on the financial sustainability of banks is analyzed. The article discloses the main current tendencies of bank lending to corporate clients, including industrial enterprises, analyzes their impact on ensuring the proper level of financial sustainability of banks. The article proposes an author’s vision as to how the credit relations of banks and industrial enterprises should change, taking into account the experience of their cooperation in previous years and taking into account the modern realities of the national economy.